Сейчас я вас a)tg(180°-d)/ctg(90°-d)= b)sin(п-d)/tg(п+d)= c)cos2(90°-d)-1/cos(180°-d)= d)sin2(180°-d)-1/cos(360°-d)= e)tg(п-d)/ctgп/2-d)= g)ctg(п+d)cos(90°-d)/tg(3п/2-d)=

iloveyou27 iloveyou27    3   17.05.2019 13:50    0

Ответы
melashich2004 melashich2004  10.06.2020 18:25

\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\


Сейчас я вас a)tg(180°-d)/ctg(90°-d)= b)sin(п-d)/tg(п+d)= c)cos2(90°-d)-1/cos(180°-d)= d)sin2(180°-d
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра